The Words of Medicine : Sources, Meanings, and Delights. - Fortuine, Robert (Charles C Thomas Publisher, LTD, 2000)
This book is a history of the medical vocabulary presented in topical (rather than dictionary) form. While most other books on medical words are arranged as dictionaries, rather than topically, and are much more selective in their presentation, this book entertains a comprehensive and historical approach to the subject. It is written primarily for physicians, biomedical scientists, and medical students, but should also appeal to anyone in the health professions or biological sciences with a 'feel' for medical history and the English language. It will also be useful to some teachers of English.